Cell Cycle and Senescence Regulation by Podocyte Histone Deacetylase 1 and 2. Issue 3 (22nd March 2023) - Medina Rangel, Paulina X.; Cross, Elizabeth; Liu, Chang; Pedigo, Christopher E.; Tian, Xuefei; Gutiérrez-Calabrés, Elena; Nagata, Soichiro; Priyadarshini, Anupama; Lerner, Gabriel; Bunda, Patricia; Perincheri, Sudhir; Gu, Jianlei; et al.
Abstract : Abstract : Significance Statement: The loss of integrity of the glomerular filtration barrier results in proteinuria that is often attributed to podocyte loss. Yet how damaged podocytes are lost remains unknown. Germline loss of murine podocyte-associated Hdac1 and Hdac2 ( Hdac1/2 ) results in proteinuria and collapsing glomerulopathy due to sustained double-stranded DNA damage. Hdac1/2 deletion induces loss of podocyte quiescence, cell cycle entry, arrest in G1, and podocyte senescence, observed both in vivo and in vitro . Through the senescence secretory associated phenotype, podocytes secrete proteins that contribute to their detachment. These results solidify the role of HDACs in cell cycle regulation and senescence, providing important clues in our understanding of how podocytes are lost following injury. Background: Intact expression of podocyte histone deacetylases (HDAC) during development is essential for maintaining a normal glomerular filtration barrier because of its role in modulating DNA damage and preventing premature senescence. Methods: Germline podocyte-specific Hdac1 and 2 ( Hdac1 / 2 ) double-knockout mice were generated to examine the importance of these enzymes during development. Results: Podocyte-specific loss of Hdac1 / 2 in mice resulted in severe proteinuria, kidney failure, and collapsing glomerulopathy. Hdac1 / 2 -deprived podocytes exhibited classic characteristics of senescence, such as senescence-associated β-galactosidase activity and lipofuscin aggregates. In addition, DNA damage, likely caused by epigenetic alterations such as open chromatin conformation, not only resulted in podocyte cell-cycle entry as shown in vivo by Ki67 expression and by FUCCI-2aR mice, but also in p21-mediated cell-cycle arrest. Through the senescence secretory associated phenotype, the damaged podocytes secreted proinflammatory cytokines, growth factors, and matrix metalloproteinases, resulting in subsequent podocyte detachment and loss, evidenced by senescent podocytes in urine. Conclusions: Hdac1 / 2 plays an essential role during development. Loss of these genes in double knockout mice leads to sustained DNA damage and podocyte senescence and loss.